Students' Note-Taking Patterns and Practices in Science Classes: A Narrative Inquiry - Piloton-Narca , Manilyn; Alda, Rivika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Note-taking is a common practice seen in every learning environment. Although common, note-taking is an important foundational skill that empowers students to actively engage in their learning process. This study aims to explore the experiences and practices of note-taking patterns of junior high school students, specifically in science classes. This is a descriptive qualitative study using a narrative inquiry approach involving 20 junior high school science students selected through purposive sampling. Data were collected through semi-structured interviews, document analysis, and interviews. Data analysis used the Braun and Clarke thematic analysis method. Through document and thematic analysis, the findings revealed four main themes: approaches to note-taking, perceptions of note-taking use, effectiveness and impact of note-taking, and improvements in note-taking practices to enhance learning. The findings indicate that students have regular note-taking habits and implement best practices for effective note-taking. It is concluded that note-taking in science classes increases student engagement and comprehension, thus supporting their academic success. Therefore, educators should encourage effective note-taking habits among students and equip them with skills that not only improve learning outcomes but also promote retention and lifelong learning.